PARENTING CERDAS UNTUK ORANGTUA: STRATEGI PENGASUHAN EFEKTIF PADA PERIODE GOLDEN AGE ANAK - Amaliyah, Shofwatun; Trisnadewi, Benedicta Audrey Putri (JPMUJ, 2026)
The golden age is a crucial period in child development that is strongly influenced by the quality of parental caregiving. However, many parents still lack adequate understanding of effective parenting strategies that align with early childhood developmental stages. This community service program aimed to enhance parents’ knowledge and skills in implementing effective parenting during the golden age through the “Smart Parenting for Parents” seminar program. The activity was conducted on January 31, 2026, in collaboration with Semarang Zoo as a partner, involving approximately 700 participants from the Kaliwungu district. The method applied was participatory psychoeducation through parenting seminars for parents combined with a colouring competition designed as a creative and developmental stimulation activity for children. The results showed high participant enthusiasm and increased parental understanding regarding positive parenting practices, effective communication, and active parental involvement in children’s activities. Additionally, the program provided enjoyable learning experiences for children through creative engagement. This program is expected to serve as a model for community service initiatives that strengthen the role of families in early childhood caregiving during the golden age.